2020
DOI: 10.5430/jnep.v10n10p33
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of implementing evidence based practices guidelines regarding blood transfusion on quality of nursing care and patients' safety in Pediatric Units

Abstract: Background and objective: The new trend that widely accepted in health care institutions is to implement an evidence-based practice. Health facilities frequently integrate standards of practice that reveal current best evidence to increase patients’ outcomes and consequently decrease hospital cost. Transfusion of blood is a cornerstone in managing many critically ill children. However, nurses have a chief role in transfusing blood and their knowledge and performance are important for them to transfuse blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This interpretation was supported by Mohammed et al, (2021) who revealed that, there was a statistically significant difference between nurses practice sub items scores regarding food &fluid management & skin care for patient with diarrhea before and after implementation of health education. (37) Also, it was supported by El-Sayed et al, (2018) regarding care of ICU patients with diarrhea. Who illustrated that there was a marked improvement in the nurses' total practices regarding management of hypovolemic shock related to sever diarrhea pre-and post-implementation of the training guidelines.…”
Section: Patients' Assessment During Icu Diarrheamentioning
confidence: 89%
See 1 more Smart Citation
“…This interpretation was supported by Mohammed et al, (2021) who revealed that, there was a statistically significant difference between nurses practice sub items scores regarding food &fluid management & skin care for patient with diarrhea before and after implementation of health education. (37) Also, it was supported by El-Sayed et al, (2018) regarding care of ICU patients with diarrhea. Who illustrated that there was a marked improvement in the nurses' total practices regarding management of hypovolemic shock related to sever diarrhea pre-and post-implementation of the training guidelines.…”
Section: Patients' Assessment During Icu Diarrheamentioning
confidence: 89%
“…This tool was developed by the researcher based on literatures review (34)(35)(36)(37) It was used for assess nurses' practice pre, immediate and 2 months later post implementation of educational program regarding intensive care units induced diarrhea; it was including the following:…”
Section: Tool (Ii) An Observational Checklist Regarding Nurses' Practicementioning
confidence: 99%